2005
DOI: 10.1002/ar.a.20202
|View full text |Cite
|
Sign up to set email alerts
|

Reelin immunoreactivity in lymphatics and liver during development and adult life

Abstract: Reelin, a glycoprotein secreted by Cajal-Retzius cells, is crucial for cortex lamination and cell positioning. Some peripheral reelin expression has also been reported. Here we describe in developing rat and human and in adult rat very definite reelin immunolocalization in two cell types. Reelin was present in endothelial cells of lymphatic vessels, but not of blood vessels. Reelin was also detected in stellate (Ito) cells of the liver as shown by immunoelectron microscopic examination. The immunlocalization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…105 Reelin, a glycoprotein secreted by Cajal-Retzius cells, is a serine protease of the extracellular matrix, which rapidly degrades fibronectin and laminin. 106 The immunohistochemical staining in human and rat fetus demonstrated the expression of reelin on LECs, but not on BECs, 107 indicating it may contribute to the special phenotype both during lymphangiogenesis and in mature lymphatics. Kaposi's sarcoma-associated herpesvirus infection of human dermal microvascular endothelial cells induces significant upregulation of the lymphatic lineage-specific gene, reelin, 108 indicating the origin of Kaposi's sarcoma from LECs.…”
Section: Integrins Endostatin Reelin Il-7 Mmps and Lymphaticsmentioning
confidence: 98%
“…105 Reelin, a glycoprotein secreted by Cajal-Retzius cells, is a serine protease of the extracellular matrix, which rapidly degrades fibronectin and laminin. 106 The immunohistochemical staining in human and rat fetus demonstrated the expression of reelin on LECs, but not on BECs, 107 indicating it may contribute to the special phenotype both during lymphangiogenesis and in mature lymphatics. Kaposi's sarcoma-associated herpesvirus infection of human dermal microvascular endothelial cells induces significant upregulation of the lymphatic lineage-specific gene, reelin, 108 indicating the origin of Kaposi's sarcoma from LECs.…”
Section: Integrins Endostatin Reelin Il-7 Mmps and Lymphaticsmentioning
confidence: 98%
“…The stellate cells of the fetal liver express desmin [23,24], β3-integrin, nestin [24], CRBP-1 [25], N-CAM [26], and reelin [27]. Some researchers consider that these cells are derived from mesenchymal cells of septum transversum, which form the submesothelial layer under the liver capsule [26,28,29], but their epithelial origin cannot be excluded [30].…”
Section: Hepatic Stellate Cellsmentioning
confidence: 99%
“…It has been suggested that defects in this pathway impair brain development and contribute to the pathogenesis of Alzheimer disease (9). Further studies have demonstrated that some extraneuronal tissues also express reelin (10), suggesting a biological role(s) of reelin beyond neuronal development.…”
mentioning
confidence: 99%